Math and science for young children - Charlesworth, Rosalind (Boston, Massachusetts : Cengage Learning Asia Pte Ltd, 2016)
Presents an introduction to engaging math and science experiences for early childhood and early elementary education programs, and provides an organized, sequential approach to creating a developmentally appropriate math and science curriculum.
Part1. Concept development in mathematics and science -- Part2. Fundamental concepts and skills -- Part3. Applying fundamental concepts -- Part4. Symbols and higher-level concepts and activities -- Part5. Mathematics concepts and operations for the primary grades -- Part6. Investigations in primary science -- Part7. The math and science environment
Includes bibliographical references and index.
Keywords: MATHEMATICS